2017
DOI: 10.1002/ange.201708921
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Reactions of CO2 and Indium‐Silylamides and Catalytic Synthesis of Ureas

Abstract: The indium compounds In(N(SiMe 3 ) 2 ) 2 Cl·THF (2) and In(N(SiMe 3 ) 2 )Cl 2 ·(THF) n (3)w ere shown to react with CO 2 to give [(Me 3 Si) 2 N)InX(m-OSiMe 3 )] 2 (X = N(SiMe 3 ) 2 4, Cl 5). 0.05-2.0 mol %ofthe species 3 acts as apre-catalyst for the conversion of aryl and alkyls ilylamines under CO 2 (2-3atm) to give the corresponding ureas in 70-99 %y ields.A proposed mechanism is supported by experimental and computational data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In the case of the photoreaction under 13 CO 2 , the peak intensity of the carboxyl carbon clearly increased, suggesting that the carboxyl moiety in DBA originates from CO 2 (Fig. 5b ) 14 , 65 .
Figure 5 13 C NMR (CD 3 CN, 126 MHz) spectra of the photochemical product ( λ ex = 300 ± 10 nm) of 1 under ( a ) CO 2 and ( b ) 13 CO 2 in THF at room temperature.
…”
Section: Resultsmentioning
confidence: 97%
“…In the case of the photoreaction under 13 CO 2 , the peak intensity of the carboxyl carbon clearly increased, suggesting that the carboxyl moiety in DBA originates from CO 2 (Fig. 5b ) 14 , 65 .
Figure 5 13 C NMR (CD 3 CN, 126 MHz) spectra of the photochemical product ( λ ex = 300 ± 10 nm) of 1 under ( a ) CO 2 and ( b ) 13 CO 2 in THF at room temperature.
…”
Section: Resultsmentioning
confidence: 97%
“…We also investigated the pathway for the formation of urea derivatives. The recent reports showed that the reactions of silylamines with CO 2 provide urea derivatives by Stephan and co‐workers, [ 24 ] therefore we carried out a reaction of (EtO) 3 SiH with N ‐methylaniline ( 1a ) at 120 o C in the presence of Zn powder. No silylamine forms, indicating the urealation of amine does not proceed through a silylamine intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…Reactions of silylamines with CO 2 provide a way to synthesise the urea derivatives under mild conditions. [ 24 ] However, silylamines are less accessible compared to primary amines, and actually silylamines are generally synthesised from the deprotonation of primary amines with n ‐BuLi followd by the treament with Me 3 SiCl. Polymer‐immobilized gold nanoparticle catalysts are able to catalyse the urealation of cyclohexylamine and benzylamine under high CO 2 pressure (50 atm) at high temperature (180 °C).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Catalytic conversions of nontoxic CO 2 to symmetric urea derivatives have also been studied. 6 However, the development of ubiquitous synthesis methods of urea derivatives using readily available raw materials is still a significant challenge and it always requires us to think outside the box.…”
Section: Introductionmentioning
confidence: 99%